Pengaruh Struktur Kepemilikan dan Pajak Perusahaan Terhadap Pembayaran Dividen - Dara Ayu Nianty (Bongaya Journal for Research in Accounting (BJRA), 2019)
This research aims to analyze the managerial structure and tax on the dividen payment. This research applied quantitative method in revealing the data, using secondary data in the form of financial statement. Population in this research derived from Stock Indonesian Exhange (BEI) in manufacturing company since 2014-2016. The analysis technique of data used in this research was multiple regression analysis technique. The researcher concluded that the testing of hypotheses in the research indicated that managerial structure and tax significant and positive of dividen payment.